The Comparative Multimodal Discourse Analysis of Advertisement in three ASEAN Countries: Myanmar, Indonesia and Thailand - Shinta Ayu Mahardiyanis; Audia Nur Safarah; Wawan Gunawan (International Journal of Science and Society, 2026)
This study focuses on multimodal discourse analysis (MDA) of advertisements in three ASEAN countries: Myanmar, Indonesia, and Thailand. The aim of this study is to identify significant differences between Myanmar, Indonesia and Thailand’s advertisements and the messages that they convey in each country. This study used a qualitative descriptive method, focusing on detailed observation and analysis of video advertisements. The results show variations in every aspect of the genre including field, mode, and tenor that reflect the cultural and social values ​​of each country. In addition, this study also reveals the ideology represented in the advertisements, which contributes to a deeper understanding of how advertisements function not only as a marketing tool but also as a media to convey social and cultural messages. Advertisements from Myanmar, Indonesia, and Thailand reflect unique cultural values ​​through distinct approaches in narrative, visuals, and ideology. Myanmar emphasizes progress and innovation, Indonesia highlights warmth and togetherness, while Thailand focuses on joy and quality. These strategies effectively convey their messages and resonate with their respective audiences, showcasing the cultural identity of each country. The finding of this study is the importance of considering the context of cultural analysis in advertising, as well as empowerment for marketing practitioners in designing more effective campaigns in the ASEAN market.